What Really Happened Here? Dealing with Uncertainty in the Book of Distance: A Critical Historiography Perspective - Haahr, Mads (Springer Verlag, 2023)
Uncertain cultural heritage presents a dilemma in its narrative representation. History seeks to push a grand narrative, at the expense of less convenient narratives. Critical historiographic approaches favor the consideration of multiple narratives as they focus on the mediation of history rather than arriving at a single truth. Virtual Reality Interactive Narratives, such as The Book of Distance, exemplify how uncertainty can be represented through re-enactment. In this late breaking work, we provide a close reading of The Book of Distance through the lens of critical historiography and suggest improvements for future similar experiences.
Lecture Notes in Computer Science (LNCS)
International Conference for Interactive Digital Storytelling (ICIDS)
Keywords: Interactive Digital Narratives; Virtual Reality; History; Critical Historiography; Creative Technologies; Digital Humanities